2012
DOI: 10.1051/0004-6361/201218902
|View full text |Cite
|
Sign up to set email alerts
|

The remnant of supernova 1987A resolved at 3-mm wavelength

Abstract: Context. The proximity of core-collapse supernova 1987A (SN 1987A) in the Large Magellanic Cloud (LMC) and its rapid evolution make it a unique case study of the development of a young supernova remnant. Aims. We aim at resolving the remnant of SN 1987A for the first time in the 3-mm band (at 94 GHz). Methods. We observed the source at 3-mm wavelength with a 750-m configuration of the Australia Telescope Compact Array (ATCA). We compared the image with a recent 3-cm image and with archival X-ray images.Result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 21 publications
4
24
0
Order By: Relevance
“…The ring flux densities are shown in Fig. 5, along with previous measurements of the ring from ALMA and the Australia Telescope Compact Array (ATCA): 1.4 GHz, 18 GHz, 44 GHz ); 9 GHz ; 94 GHz (Lakićević et al 2012). As the frequency increases towards the submm and FIR, the contribution of the thermal ejecta emission to the total emission becomes more significant, so the ring emission at day 9280 was estimated from the total flux densities at 102, 213, 345, & 672 GHz by scaling and subtracting an ejecta model component in Fourier space based on the Band-9 ejecta flux density at each frequency .…”
Section: The Ringmentioning
confidence: 89%
See 2 more Smart Citations
“…The ring flux densities are shown in Fig. 5, along with previous measurements of the ring from ALMA and the Australia Telescope Compact Array (ATCA): 1.4 GHz, 18 GHz, 44 GHz ); 9 GHz ; 94 GHz (Lakićević et al 2012). As the frequency increases towards the submm and FIR, the contribution of the thermal ejecta emission to the total emission becomes more significant, so the ring emission at day 9280 was estimated from the total flux densities at 102, 213, 345, & 672 GHz by scaling and subtracting an ejecta model component in Fourier space based on the Band-9 ejecta flux density at each frequency .…”
Section: The Ringmentioning
confidence: 89%
“…The literature values for the total SN 1987A flux densities at various wavelengths are shown as grey hexagons, and represent the overall spectral energy distribution (SED) of the system. The total emission at 1.4 GHz, 18 GHz, 44 GHz (Zanardo et al 2013), 9 GHz , 94 GHz (Lakićević et al 2012), and 102 GHz ) is dominated by synchrotron emission from the ring. The total emission at 213, 345, & 672 GHz ), on the other hand, gradually consists of a higher and higher fraction of thermal emission until that is dominant in the submm Figure 5.…”
Section: Photometrymentioning
confidence: 99%
See 1 more Smart Citation
“…More recently Matsuura et al (2011) have from Herschel far-IR observations found evidence for a large dust mass, estimated to 0.4 − 0.7 M ⊙ , but could be up to 2.4 M ⊙ . The mass estimate is, however, highly dependent on the dust temperature and the mass could be several orders of magnitude lower if the temperature is higher than adopted by Matsuura et al (2011), as discussed from APEX observations by Lakićević et al (2012).…”
Section: Dustmentioning
confidence: 98%
“…Observations at higher frequencies (18, 36, 44 and 94 GHz) undertaken with ATCA (Manchester et al 2005;Potter et al 2009;Lakićević et al 2012;Zanardo et al 2013), followed by observations at 110, 215, and 345 GHz with the Atacama Millimeter/Submillimeter Array (ALMA), show the same asymmetric double lobe morphology Zanardo et al 2014). Also ALMA observations revealed the presence of one of the largest masses of cold dust (greater than 0.2 M ) ever measured in a SNR.…”
Section: Supernova Remnants In the Magellanic Cloudsmentioning
confidence: 81%